El clima organizacional y su influencia en el mejoramiento del desempeño laboral de los trabajadores del Ministerio Público de Cajabamba - Salirrosas Alayo, Cristina Lizet (2022)
The thesis determines the influence of the organizational climate on the work performance of the workers of the Public Ministry of Cajabamba, for which a set of theories related to the organizational climate and its direct relationship with work performance was established and structured. As a research hypothesis, it maintains that the organizational climate significantly influences the improvement of the work performance of the workers of the Public Ministry of Cajabamba; Being a basic level investigation because it aims to know, explain and understand the phenomena based on the existing previous information, it is of a non-experimental descriptive type, limiting itself to observing the events without intervening in them, in the same way it is correlational: because they find the relationship between two variables: organizational climate and job performance; It is also a transactional investigation since the study is carried out at a certain time, the study population and sample is 38 workers, a questionnaire was used as a data collection technique. The results establish that, between the organizational climate and the work performance of the workers of the Public Ministry of Cajabamba, there is a high positive correlation (Spearman's Rho ,839), from which it is deduced as a conclusion that the organizational climate influences the improvement of the labor performance of the workers of the Public Ministry of Cajabamba. On the other hand, its levels are determined to be regular; so it is recommended to invest in human talent; in order to increase their levels and be more favorable and achieve a good level of performance.